(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:A spontaneous recessive mutation in the gene coding for protein kinase gamma has created a new rat strain called Albino Swiss/ Anatomy Glasgow University (AS/AGU). It characterized by disordered locomotion due to impaired dopamine release from certain areas of the brain and eventual neurodegeneration. The mutant rats also have a shorter life span. Objective:The present study investigates Lipofuscin level as an indicator of age and calbindin D-28k level as an indicator of neuronal integrity in cerebellar Purkinje cells of the mutant AS/AGU strain in comparison to the normal AS strain. Methods:Eighteen rats (9 AS and 9 AS/AGU) were selected to study the Lipofuscin and calbindin in relation to age and strain using multiple histological techniques including fluorescent microscopy. Results:Fluorescent microscopical study has shown early age related Lipofuscin accumulation in the AS/AGU rats compared to the normal strain. Moreover, Calbindin D-28k showed age related increase in both strains but marginally significant decline in the AS/AGU strain. Conclusions:Our study presents AS/AGU as an animal model of early aging in addition to its value as a model of neurodegeneration. Keywords:Aging, Albino Swiss Rat, Calbindin D-28k, Fluorescent Microscopy, Lipofuscin.